2012
DOI: 10.1534/genetics.111.132266
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin and Transcription in Yeast

Abstract: Understanding the mechanisms by which chromatin structure controls eukaryotic transcription has been an intense area of investigation for the past 25 years. Many of the key discoveries that created the foundation for this field came from studies of Saccharomyces cerevisiae, including the discovery of the role of chromatin in transcriptional silencing, as well as the discovery of chromatin-remodeling factors and histone modification activities. Since that time, studies in yeast have continued to contribute in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
263
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(272 citation statements)
references
References 553 publications
(726 reference statements)
9
263
0
Order By: Relevance
“…Over millions of years, eukaryotes have incorporated chromatin structure into the regulation of many aspects of DNA metabolism, from simple nuclear packaging to transcriptional control (2). This diversity of purpose is reflected in two general types of chromatin structures within the nucleus-euchromatin, which is decondensed and transcriptionally active, and heterochromatin, which is typically localized to the nuclear periphery and repressive for DNA recombination and transcription.…”
mentioning
confidence: 99%
“…Over millions of years, eukaryotes have incorporated chromatin structure into the regulation of many aspects of DNA metabolism, from simple nuclear packaging to transcriptional control (2). This diversity of purpose is reflected in two general types of chromatin structures within the nucleus-euchromatin, which is decondensed and transcriptionally active, and heterochromatin, which is typically localized to the nuclear periphery and repressive for DNA recombination and transcription.…”
mentioning
confidence: 99%
“…The in vivo nucleosome eviction activity of such chromatin remodelling complexes has been shown to require histone chaperones to tether the evicted histones [7]. One of the best characterised histone chaperones is Asf1, which coordinates nucleosome dynamics at gene promoters and open reading frames [33,34].…”
Section: How Could Histone Acetylation Promote Histone Eviction?mentioning
confidence: 99%
“…The histone modifications most commonly associated with active gene transcription are histone acetylation and histone methylation [7]. Numerous enzymes have been identified that can catalyse the addition and removal of most of these modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I n eukaryotic nuclei, DNA is wrapped around histones to form nucleosomes, the basic subunits of chromatin (1). The physical and chemical properties of chromatin are regulated by at least two types of enzymatic activities: chromatin remodeling and posttranslational modifications of histones and chromatin-associated proteins (2,3). These enzymatic activities directly determine the accessibility of DNA for transcription, replication, and repair.…”
mentioning
confidence: 99%